Rebounding from Corruption: Perceptions of Ethics Program Effectiveness in a Public Sector Organization - Pelletier, Kathie L. (Journal of business ethics, 2006)
We examine the perceived importance of three organizational preconditions (awareness of formal ethics codes, decision-making techniques, and availability of resources) theorized to be critical for ethics program effectiveness. In addition, we examine the importance of ethical leadership and congruence between formal ethics codes and informal ethical norms in influencing employee perceptions. Participants (n=418) from a large southern California government agency completed a survey on the perceived effectiveness of the organization’s ethics program. Results suggest that employee perceptions of organizational preconditions, ethical leadership and informal ethical norms were related to perceptions of ethics program effectiveness. Based on these findings, organizations should evaluate the presence (or absence) of essential preconditions and take steps to ensure that leaders model espoused organizational values to foster perceptions of effective ethics programs.